2023
DOI: 10.1021/acs.langmuir.3c01752
|View full text |Cite
|
Sign up to set email alerts
|

Studying the Adsorption of Gas Molecules and Defects on Modulating the Electronic Transport Characteristics of Monolayer Penta-BN2-Based Devices

Ning Yang,
Tong Chen,
Zhonghui Xu
et al.

Abstract: Two-dimensional atomic layer materials, as an important part of the post-Moore era, have recently become an ideal choice for the preparation of high-efficiency, low-power, and miniaturized gas sensors. In this work, our study utilized density functional theory and the nonequilibrium Green's function method to investigate the electronic properties of the pentagonal BN 2 (P-BN 2 ) monolayer, as well as its gas-sensing properties for organic and inorganic gases. We also investigated how defects affect the quantum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Liu et al demonstrated that bent T-graphene has Dirac cone-like Fermions with the promise of T-graphene having more possibilities than graphene due to its different band structure . The multifunctionality of these graphene derivatives is promising for a wide range of applications in the fields of nanoelectronics and nanomechanics. Recently, graphene isomers have been successfully synthesized as biphenylene (BPN) by intersurface polymer dehydro-fluorination (HF-zipping) reaction, which is a purely planar mesh structure composed of tetragonal-hexagonal-octagonal shapes. , The successful synthesis of its monolayer has given rise to new thinking about 2D carbon isomers with promising applications in electrochemistry and nanoelectronics for their excellent thermal transport, stability, and electron transport properties. , …”
Section: Introductionmentioning
confidence: 99%
“…Liu et al demonstrated that bent T-graphene has Dirac cone-like Fermions with the promise of T-graphene having more possibilities than graphene due to its different band structure . The multifunctionality of these graphene derivatives is promising for a wide range of applications in the fields of nanoelectronics and nanomechanics. Recently, graphene isomers have been successfully synthesized as biphenylene (BPN) by intersurface polymer dehydro-fluorination (HF-zipping) reaction, which is a purely planar mesh structure composed of tetragonal-hexagonal-octagonal shapes. , The successful synthesis of its monolayer has given rise to new thinking about 2D carbon isomers with promising applications in electrochemistry and nanoelectronics for their excellent thermal transport, stability, and electron transport properties. , …”
Section: Introductionmentioning
confidence: 99%